Integration of Technology and Aerobics: The Effect of Interactive Video on Motivation and Exercise Consistency - Poppy Elisano Arfanda; Ians Aprilo; M. Adam Mappaompo; Arimbi (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study was motivated by the low consistency of student participation in aerobic exercise due to time constraints, limited access, and fluctuations in motivation. The use of interactive videos is seen as an innovative solution to enhance engagement in exercise in a flexible and structured manner. This study aims to analyse the effect of interactive videos on intrinsic motivation, extrinsic motivation, and exercise consistency. The method used was a quantitative approach with a quasi-experimental design involving 60 students divided into experimental and control groups. Data collection was conducted via questionnaires and observation, whilst data analysis utilised validity and reliability tests, t-tests, and linear regression. The results of the study showed that the experimental group had a higher average motivation score (3.735) compared to the control group (3.347), with a  of 3.996 and . Regarding the participation variable, the experimental group also scored higher (3.667) than the control group (3.298), with  and . Regression analysis showed that interactive videos had a significant effect on exercise consistency ( ), contributing 49.6% ( ). In conclusion, interactive videos are effective in increasing motivation and consistency in aerobic exercise and support the sustainability of students’ physical activity.